2017
DOI: 10.1007/s12094-017-1626-1
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNAs as novel serum biomarkers for the diagnosis of hepatocellular carcinoma: a systematic review and meta-analysis

Abstract: LncRNAs were a high diagnostic value for HCC and its expression could potentially be used as auxiliary biomarker in confirming HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…Alpha fetal protein (AFP) has been widely used as a diagnostic marker for HCC, but its sensitivity and specificity are suboptimal [ 92 , 93 ]. lncRNAs with a significantly aberrant expression profile in HCC tissues as opposed to healthy liver may hold great potential as diagnostic markers [ 94 ]. Some lncRNAs may be stably present in body fluids such as plasma and their expression levels are consistently associated with the progression of HCC [ 94 ].…”
Section: Role Of Lncrnas In the Regulation Of Liver Cancer Stem Cellsmentioning
confidence: 99%
“…Alpha fetal protein (AFP) has been widely used as a diagnostic marker for HCC, but its sensitivity and specificity are suboptimal [ 92 , 93 ]. lncRNAs with a significantly aberrant expression profile in HCC tissues as opposed to healthy liver may hold great potential as diagnostic markers [ 94 ]. Some lncRNAs may be stably present in body fluids such as plasma and their expression levels are consistently associated with the progression of HCC [ 94 ].…”
Section: Role Of Lncrnas In the Regulation Of Liver Cancer Stem Cellsmentioning
confidence: 99%
“…The technique for detection and measurement of specific serum lncRNAs has become feasible, which provides a new method without invasiveness for the identification of new biomarker for cancer. Recent studies found that serum lncRNAs are useful for the diagnosis of multiple types of cancer, such as bladder cancer [ 69 ], liver cancer [ 70 ], cervical cancer [ 71 ], gastric cancer [ 72 ], colorectal cancer [ 73 , 74 ] and breast cancer [ 75 ] etc, these serum lncRNAs may even serve as prognostic biomarkers [ 69 , 72 , 74 ]. Serum lncRNAs in RCC patients are also deregulated.…”
Section: Lncrnas In Rccmentioning
confidence: 99%
“…As we know that lncRNA studies are still in their infancy and the functions remain unclear. Up to now, more and more literature has proved that lncRNA expressions are involved in cancer metastasis (5,6). Brain cytoplasmic RNA 1 (BCYRN1), also called BC200, ordinarily cannot be detected in normal tissue, except for in the primate nervous system (7).…”
Section: Introductionmentioning
confidence: 99%